Sodobna slovenska poezija v literarni vedi - Novak-Popov, Irena (Slavistična revija, 2013)
This survey does not pretend to exhaustiveness but presents the genres of scholarly writing for different audiences and purposes. In addition to strictly scholarly texts, it encompasses essayistic, interpretive, and scholarly treatises. Books, articles, and commentaries evidence the range of directions in this expansive, scarcely manageable sector of literary creativity. Poetry's status among literary genres is in inverse relation to its quantitative and developmental measures; it has slipped from its one-time central position to unprecedented peripherality and the domain of a select few. They are the professional cognoscenti at universities and institutes who are competent in literary discourse and employ it in specialized descriptions of select fields, as well as amateurs, including most poets, who frequently assume the role of interpreters, editors, and purveyors.
Keywords: anthologies; antologije; collections; interpretacije; interpretation; literarna veda; literary science; literary studies; Slovene literature; Slovene poetry; slovenska književnost; slovenska poezija; sodobna poezija; zbirke